The Art of Retrospection and the Country Houses of Post-Restoration Scotland. Issue 1 (November 2015) - Wemyss, Charles
Abstract : The philosophy of The Scottish Chateau undermined the established theory that the Restoration marked Scotland's emergence from the Dark Ages to a brilliant new dawn of refinement and culture. Far from isolated and barbaric, the Scottish nobility had been educated in Paris, Rome or Leiden and were as enlightened as any in Europe. Yet the idea of the defensive tower-house persists. This article argues that retrospective reference to castellated tradition in the seventeenth-century Scottish nobleman's house was rather a conscious assertion of ancestry.